Phylogenomics of sigmodontine rodents (Cricetidae: Sigmodontinae): Cloud forests and Pliocene extinction explain the timing and spread of an iconic South American radiation - Max R. Bangs; Alexandre Reis Percequillo; Víctor Pacheco; Scott J. Steppan (PLoS ONE, 2025)
Studies of biotic radiations following geographic invasions often overlook the potential role of subsequent climatic, biotic, and geologic triggers, instead focusing largely on the earliest stage of an invasion. For example, studies of the rodent subfamily Sigmodontinae, a clade of over 500 species that radiated throughout South America as an early participant in the Great American Biotic Interchange, have historically focused more on invasion than post-invasion opportunities or subsequent environmental change. Here, we place the timing and transitions of this radiation in context of changing climatic, biotic, and geologic factors by reconstructing the biogeography of the radiation. To accomplish this, we generated the largest genomic phylogeny of Sigmodontinae to date, one that includes over 80% of the genera and 40% of the known species (including all incertae sedis taxa), and we produced a fossil-calibrated chronogram. Our results indicate a single invasion of South America at the base of Sigmodontinae (~ 10.46 million years ago [mya]) with two waves of increased lineage generation and biogeographic transition rates, the first of which occurred following a four-million-year lag after the invasion. The timing and location of this initial radiation (6.61–5.78 mya, Oryzomyalia) coincided with the spread of montane cloud forest along the Andean cordillera during the Late Miocene Cooling. We propose a scenario where sigmodontines did not spread throughout the continent until the Mid-Pliocene Faunal Turnover (4.5–3.0 mya), a period of high extinction of South American mammals. A comprehensive classification for the subfamily (including two new Linnaean tribes) is provided that incorporates these new results.